(untitled)
"In this Part II, systematic descriptions and/or microphotographs of 53 species of palynomorphs from the Lower Jurassic and Aalenian (Sierra Chacai-Co Formation and Los Molles Formation) from the southern border of the Neuquén Basin are presented. They belong to the following genera: Deltoidospora, Todisporites, Dictyophyllidites, Biretisporites, Concauisporites, Auritulinasporites, Osmundacidites, Verrucosisporites, Rugulatisporites, Cadargasporites, Ceratosporites, Lycopodiumsporites, Ischyosporites, Gleicheniidites, Neoesisporites (trilete miospores); Aratrisporites (?), Peromonolites, Punctatosporites (monolete miospores); Callialasporites, V itreisporites, Alisporites, Podocarpidites (saccate pollen); Cycadopites, Monosulcites, Cerebropollenites, Equisetosporites (colpate pollen ) ; Perinopollenites, Classopollis (porate pollen